Principles of organization of the digital communication environment in the kindergarten interior - Tikunova Svetlana V.; Shcheblykina Irina V.; Sheremet Alena A.; Chekhonadskikh Nadezhda N. (Архитектон)
Digitalization in the new millennium has naturally covered all spheres of human social activity: as a child grows up, media resources are becoming not only a means of obtaining information, but also a tool of social interaction. The educational system in Russia is currently in the process of transition from traditional methods of organizing educational activities to innovative methods with the active introduction of interactive technologies. Despite a number of objective problems, such as the relatively high cost of modernization, the lack of qualified teachers, and, for the most part, the lack of an interdisciplinary approach to the organization of the environment as a whole, the use of digital technologies is regarded as an important factor in the development of education, including preschool. In practical terms, digitalization involves creating an environment that meets the needs of the younger generation, including specialized technical equipment for educational institutions. We consider principles that underlie the design of interior spaces in kindergartens of a new format with the use of digital equipment allowing for current trends in the design of such institutions.